Increasing Access to Effective Education Across Oceania - Hogan, Robert and Nimmer, Natalie (International Journal of Web-Based Learning and Teaching Technologies, 2013)
The history of education in many developing nations is a template of ineffectual and expensive instruction. Despite nearly half a century of higher education in the Pacific, up to 50% of the teachers in many countries such as the Federated States of Micronesia and the Republic of the Marshall Islands still have no more than a high school education. Similar trends are found in Asia and Africa. Past experience in Oceania demonstrates that face-to-face university training has been neither scalable nor sustainable. This paper compares two educational approaches—face-to-face and blended learning. The face-to-face, WorldTeach program in the Marshall Islands employed foreign volunteer teachers living on site to give local teachers a year’s leave for additional training. The blended chemistry course, which combined online and face-to-face learning, was delivered simultaneously to teacher candidates in Fiji, Vanuatu, and the Solomon Islands. The blended course utilized online instructors and tutors, and face-to-face tutors. This paper discusses the strengths and weaknesses of both case studies and recommends that nations consider blended learning as an approach to make education more accessible and affordable, especially in emerging nations. As brick-and-mortar campuses and instructor travel become more expensive, blended learning becomes an increasingly attractive educational option.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNDAxOC9qd2x0dC4yMDEzMDEwMTAy